Neem (Azadirachta indica A. Juss) repelencia a Cerotoma ruficornis (Olv.) y Diabrotica balteata (Lec.) (Coleoptera: Chrysomelidae) y reducción de virosis en Vigna unguiculata (L.) Walp - Gómez R, Emigdio S. (1990)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 1990